METODE PELAKSANAAN PENGASPALAN PADA PROYEK PEMELIHARAAN JALAN TALAGA – SANGIANG - Isnandar, Ence (Universitas Majalengka, 2022)
Road Maintenance Projects are activities related to road maintenance and repairs that are needed and planned to maintain road conditions so that they continue to function optimally to serve traffic during the specified road design life. Road construction maintenance work is an important job to carry out because road construction is a large capital investment so that if its implementation is neglected, it will require very expensive reconstruction costs to maintain performance standards. in the Talaga – Sangiang Road Maintenance Project, there are three work items, namely surface layer maintenance and foundation repair work, drainage work, and retaining wall work. Road Maintenance Project work with a road design age of 5 years in accordance with the Regulation of the Minister of Public Works chapter vii article 15. Pratik's work location is in the Talaga - Sangiang Road Maintenance Project because it meets the budget requirements set and the existing data can be processed to compile a report. This practical work is carried out for 6 months starting from licensing arrangements to conducting seminars with a time of ± 2 months in the field according to the time of the project. in writing the journal only discusses asphalt coating including: knowing the type of material used, understanding asphalting/road compaction techniques, knowing what tools are used, understanding the resources used in the Talaga-Sangian road maintenance project.